A Panel of Plasma Biomarkers for Differential Diagnosis of Parkinsonian Syndromes - Li, Qi; Li, Zhen; Han, Xiaoxuan; Shen, Xiao; Wang, Fei; Bai, Lipeng; Li, Zhuo; Zhang, Rui; Wang, Yanlin; Zhu, Xiaodong (Frontiers in Neuroscience, 2022)
Objective: The aim of our study is to explore the most reliable panel of plasma biomarkers for differential diagnosis of Parkinsonian syndromes (PDS). We selected five kinds of neurodegenerative proteins in plasma: neurofilament light chain (NfL), α-synuclein (α-syn), total-tau, and β-amyloid 42 (Aβ42) and β-amyloid 40 (Aβ40) and investigated the diagnostic value of these biomarkers. Methods: A total of 99 plasma samples from patients with Parkinson’s disease (PD), multiple system atrophy (MSA), progressive supranuclear palsy (PSP), and age-matched healthy controls (HC) were enrolled in our study. Plasma NfL, α-syn, total-tau, Aβ42, and Aβ40 levels was quantified by ultrasensitive single molecule array immunoassay. We used logistic regression analyses to examine diagnostic accuracy of these plasma biomarkers. Disease severity were assessed by the modified Hoehn and Yahr staging scale (H&Y stage), Unified Parkinson’s Disease Rating Scale part III (UPDRS III) and the Mini-Mental State Examination (MMSE), and subsequently, correlation analysis was performed. Results: A combination of α-syn, Aβ42, Aβ40, Aβ42/40 and NfL could achieve a best diagnostic value in differentiating PDS from HC and PD from HC, with an AUC of 0.983 and 0.977, respectively. By adding NfL to measurements of α-syn or Aβ42 or Aβ40 or Aβ42/40, the best discriminating panel was formed in differentiating APD and HC and the discriminatory potential could reached a sensitivity of 100% and specificity of 100% (AUC 1.000). For further distinguishing PD from APD, we found a combination of NfL, Aβ42 and total-tau was the most reliable panel with equally high diagnostic accuracy. With respect to differentiating the subtypes of APD from one another, our results revealed that measurement of NfL, total-tau, Aβ42, Aβ40 and Aβ42/40 was the best discriminating panel. Correlation analysis suggested that plasma Aβ42 levels were positively correlated to UPDRS part III scores in MSA. In terms of cognitive function, there was a relationship between plasma Aβ42/40 level and MMSE scores in patients with APD. Conclusions: In our study, various combinations of plasma biomarkers have great potentialities in identifying PDS, with important clinical utility in improving diagnostic accuracy. Plasma NfL may have added value to a blood-based biomarker panel for differentiating PDS.